Efektivitas Pemungutan Pajak Bumi dan Bangunan di Kantor Kelurahan Bongohulawa Kecamatan Limboto Kabupaten Gorontalo - Kuke, Sri Dewanti; Isa, Rusli; Tantu, Romy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this research is to describe the effectiveness of Land and Building tax collection in at the office of Bongohulawa village, Limboto subdistrict of Gorontalo Regancy, according to four indicators; input, throughput, output, and outcome. The object is the office og Bongohulawa village in Limboto Subdistrict of Gorontalo Regency. This is a descriptive qualitative research, the data is collected through observation, interviews, and documentation to be analysed qualitatively. The result of this research shows that (1) the input had been done effectively according to the procedures established by the office, (2) throughput or informing about the land and building tax by giving the tax return to every head of the villages to facilitate the payment at the post office, bank, or directly to the head of the village, (3) the output indicator shows that the tax collection had not done according to the target, and (4) outcome indicatortells that the tax payment procedures and mechanism implemented at the office had been done effectively. Therefore, according to the result above it can be concluded that the effectiveness of Land and Building tax collection had not been done effectively and led to the tax revenue target unachieved. It means that not all the people living in Bongohulawa village were aware of the tax payment, and that it is recommended to recognize the important of settling the tax payment.